Pengaruh Sistem Pengendalian Internal dan Kompetensi Aparatur Terhadap Akuntabilitas Pengelolaan Dana Desa Melalui Siskeudes Sebagai Variabel Intervening pada Pemerintah Desa di Kecamatan Suwawa Kabupaten Bone Bolango - Rahmat Rianto Yusuf; Harun Blongkod; Ayu Rakhma Wuryandini (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to analyze the influence of internal control systems and apparatus competence on the accountability of village fund management through the Village Financial System (Siskeudes) as an intervening variable in village governments in Suwawa District, Bone Bolango Regency. This study employed a quantitative approach using survey methods through questionnaires distributed to village officials. Data were analyzed using statistical analysis to examine the relationships among variables. The results show that internal control systems and apparatus competence have a significant effect on the accountability of village fund management. Internal control systems also significantly affect the implementation of Siskeudes, while apparatus competence has no significant effect on Siskeudes. Furthermore, Siskeudes has no significant effect on the accountability of village fund management and is unable to mediate the relationship between internal control systems and apparatus competence on accountability. This study confirms that improving village fund management accountability is more influenced by strengthening internal control systems and apparatus competence rather than relying solely on application systems.